Development of Spectrophotometric method for quantitative determination of dexamethasone in pharmaceutical preparations - Rafal Abdulraheem Abdullah; Khalaf F. AL-Samarraee (Tikrit Journal of Pure Science, 2023)
This Study is concerned a fast, easy, sensitive, accurate and economical spectrophotometric method for the determination of Dexamethasone. This method based on the use of UV- spectra measurements at 242 nm.